Correction: Compressible colloidal clusters from Pickering emulsions and their DNA functionalization. Issue 77 (14th September 2018) - Jo, In-Seong; Oh, Joon Suk; Kim, Shin-Hyun; Pine, David J.; Yi, Gi-Ra
Abstract : Correction for 'Compressible colloidal clusters from Pickering emulsions and their DNA functionalization' by In-Seong Jo et al., Chem. Commun., 2018, 54, 8328–8331.